2019
DOI: 10.4269/ajtmh.19-0098
|View full text |Cite
|
Sign up to set email alerts
|

Early Mortality among Immunocompetent Patients of Tuberculous Meningitis: A Prospective Study

Abstract: Most deaths in tuberculous meningitis occur in the early part of the illness. We assessed the determinants of early deaths, occurring within 2 months of intensive therapy. We prospectively included consecutive newly diagnosed adults with HIV-negative tuberculous meningitis. Patients were given WHO-recommended antituberculosis treatment and were followed up for 9 months. We enrolled 152 patients. A total of 26 deaths were recorded during 2 months. The logistic regression analysis revealed that papilledema (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
4
8
2
Order By: Relevance
“…Although Glasgow coma scale has been introduced to evaluate the severity and predict the outcome of TBM 21 and a low Glasgow coma scale (GCS) score on admission was associated with a poor prognosis, the accurate criteria (score cut-off) for this is not well characterized. For example, GCS (score: 3-8) is thought as an independent predictor of poor outcome in TBM patients 22 ; the scale with ≤ 10 has a poor outcome 23 . In contrast, compared with Glasgow coma scale, coma as a symptom may be easy to use in the management of childhood TBM.…”
Section: Discussionmentioning
confidence: 99%
“…Although Glasgow coma scale has been introduced to evaluate the severity and predict the outcome of TBM 21 and a low Glasgow coma scale (GCS) score on admission was associated with a poor prognosis, the accurate criteria (score cut-off) for this is not well characterized. For example, GCS (score: 3-8) is thought as an independent predictor of poor outcome in TBM patients 22 ; the scale with ≤ 10 has a poor outcome 23 . In contrast, compared with Glasgow coma scale, coma as a symptom may be easy to use in the management of childhood TBM.…”
Section: Discussionmentioning
confidence: 99%
“…While younger age and HIV coinfection were associated with microbiologically proven CNS-TB, older age was associated with increased mortality (34). Diabetes mellitus, chronic kidney failure, presence of hydrocephalus and microbiologically-confirmed CNS-TB were independent risk factors for increased mortality (19,32,(34)(35)(36)(37).…”
Section: Epidemiology Of Cns-tbmentioning
confidence: 99%
“…Tuberculous meningitis (TBM) is thought of as one of the serious forms of TB disease. It was reported that 15%-30% of children with TBM died [2][3][4], and survivors are easy to have neurological disabilities [5,6]. Therefore, timely diagnosis and appropriate treatment are required to improve the current dilemma of the disease.…”
Section: Introductionmentioning
confidence: 99%